ACUTE PANCREATITIS AND HEPATITIS CAUSED BY INFLUENZA B VIRUS INFECTION: CASE REPORT - Tjaša Žagar; Liza Lea Lah; Tina Kamhi Trop (The Society for Children with Metabolic Disorders, 2020)
We present a case of acute pancreatitis and hepatitis caused by influenza B virus infection in a child. In the search for the aetiology of the impairment of the two organs, we ruled out the most common causes of acute pancreatitis and hepatitis such as gallstones, drugs, hepatotropic viruses, and some autoimmune diseases. We concluded that in this case, inflammation of the pancreas and liver was caused by the influenza B virus. With the presentation of this case, we want to draw attention to the possibility of hepatitis and pancreatitis being caused by the influenza virus.